The Expression Pattern of the Na+ Sensor, NaX in the Hydromineral Homeostatic Network: A Comparative Study between the Rat and Mouse - Nehmé, Benjamin; Henry, Mélaine; Mouginot, Didier (Frontiers in Neuroanatomy, 2012)
The Scn7a gene encodes for the specific sodium channel NaX, which is considered a primary determinant of sodium sensing in the brain. Only partial data exist describing the NaX distribution pattern and the cell types that express NaX in both the rat and mouse brain. To generate a global view of the sodium detection mechanisms in the two rodent brains, we combined NaX immunofluorescence with fluorescent cell markers to map and identify the NaX-expressing cell populations throughout the network involved in hydromineral homeostasis. Here, we designed an anti-NaX antibody targeting the interdomain 2-3 region of the NaX channel’s α-subunit. In both the rat and mouse, NaX immunostaining was colocalized with vimentin positive cells in the median eminence and with magnocellular neurons immunopositive for neurophysin associated with oxytocin or vasopressin in both the supraoptic and paraventricular nuclei. NaX immunostaining was also detected in neurons of the area postrema. In addition to this common NaX expression pattern, several differences in NaX immunostaining for certain structures and cell types were found between the rat and mouse. NaX was present in both NeuN and vimentin positive cells in the subfornical organ and the vascular organ of the lamina terminalis of the rat whereas NaX was only colocalized with vimentin positive cells in the mouse circumventricular organs. In addition, NaX immunostaining was specifically observed in NeuN immunopositive cells in the median preoptic nucleus of the rat. Overall, this study characterized the NaX-expressing cell types in the network controlling hydromineral homeostasis of the rat and mouse. NaX expression pattern was clearly different in the nuclei of the lamina terminalis of the rat and mouse, indicating that the mechanisms involved in systemic and central Na+ sensing are specific to each rodent species